IMPLEMENTASI PERENCANAAN LABA PADA UMKM (STUDI KASUS UMKM TAKE ONE THAI TEA) - aprilia, rachma; Sofyan, Mifta (Polytechnic of State Finance STAN, 2023)
The purpose of this study is to review the implementation of profit planning by using Cost Volume Profit (CVP) analysis on SMEs. Profit planning has a positive effect on the achievement of operating profit. This research uses descriptive qualitative method with the object of SME Take One Thai Tea. SME Take One Thai Tea does simple bookkeeping on a cash basis and has never prepared financial statements. The results show that with CVP analysis, the owner can determine sales targets in rupiah and units so that they can be used as performance indicators for their employees and also as a basis for giving bonuses that can motivate employees. In addition, the owner can understand information on costs incurred in more detail that can be used in cost controlling.